Interferensi Fatis Bahasa Galela dalam Bahasa Indonesia oleh Penutur Etnis Galela - Maesyaroh Maesyaroh; Haniatul Mufidah; Nur Aulia Miza; Nala A'izatul Haira; Redika Cindra Reranta (Universitas Islam Sumatera Utara, 2026)
This study examines the syntactic structure of phatic expressions across local languages in Indonesia, with particular emphasis on the Galela language and several regional dialects in North Maluku. The research addresses how phatic elements are structurally realized and function pragmatically in maintaining social interaction and cohesion among speakers. Employing a qualitative approach, data were collected through informal interviews, field notes, audio recordings, and systematic verification to ensure analytical reliability. The findings reveal that phatic expressions occur in the form of particles, single words, phrases, and clauses, with variations shaped by local cultural contexts and dialectal differences. Specific phatic particles such as bai, to, si, and ka function as semantic intensifiers, pragmatic softeners, and markers of social proximity within discourse. The study argues that the syntactic and pragmatic integration of phatic elements reflects broader socio-cultural norms embedded in language use. These results contribute to descriptive syntax and pragmatics while providing a foundation for the development of culturally responsive local language learning materials that promote effective and harmonious communication.